Entwicklung einer Kontinuumsbeschreibung für die Versetzungsmobilität in Versetzungsnetzwerken - Sudmanns, Markus (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2020)
This work deals with the homogenization of dislocation reactions across slip systems in a physically based three-dimensional formulation of metal plasticity. Based on comparisons with discrete dislocation dynamics simulations, a description of dislocation networks is developed. Thereby, strain hardening is achieved as a consequence of the evolution of dislocation networks, which in turn results from an interaction of plastic slip and physical mechanisms.